2022
DOI: 10.3389/fonc.2022.777602
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prophylactic Administration of Granulocyte Colony-Stimulating Factor on Peripheral Leukocyte and Neutrophil Counts Levels After Chemotherapy in Patients With Early-Stage Breast Cancer: A Retrospective Cohort Study

Abstract: BackgroundBoth chemotherapy-induced neutropenia (CIN) and febrile neutropenia (FN) frequently occur and can lead to dose-limiting toxicity and even fatal chemotherapy side effects. The prophylactic use of recombinant human granulocyte colony-stimulating factor (rhG-CSF), including pegylated rhG-CSF (PEG-rhG-CSF), significantly reduces the risks of CIN and FN during chemotherapy in early-stage breast cancer (ESBC) patients. However, whether the prophylactic use of granulocyte colony-stimulating factor (G-CSF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
4
0
2
Order By: Relevance
“…[34] Those with complications such as hydrothorax or ascites have a worse prognosis. Due to the routine preventive application of leukopenia drugs, fewer patients delayed treatment due to leukopenia, [35][36][37] so we did not include white blood cell suppression in the model. In summary, hemoglobin suppression grade, platelet suppression grade, and liver function classi cation were included in the nal model.…”
Section: Clinical E Cacy Analysismentioning
confidence: 99%
“…[34] Those with complications such as hydrothorax or ascites have a worse prognosis. Due to the routine preventive application of leukopenia drugs, fewer patients delayed treatment due to leukopenia, [35][36][37] so we did not include white blood cell suppression in the model. In summary, hemoglobin suppression grade, platelet suppression grade, and liver function classi cation were included in the nal model.…”
Section: Clinical E Cacy Analysismentioning
confidence: 99%
“…Those with complications such as hydrothorax or ascites have a worse prognosis. Due to the routine preventive application of leukopenia drugs, fewer patients delayed treatment due to leukopenia [35][36][37], so we did not include white blood cell suppression in the model. In summary, hemoglobin suppression grade, platelet suppression grade, and liver function classi cation were included in the nal model.…”
Section: Clinical Utility Analysismentioning
confidence: 99%
“…Different types of white blood cells participate in the body's immune defense response in different ways. A previous retrospective study has provided preliminary evidence of a conceivable correlation between peripheral leukocyte and neutrophil counts and the clinical attributes of BC patients 19 . Larsson et al 20 reported significant associations between peripheral blood mononuclear cell populations and prognosis in patients afflicted with metastatic BC.…”
Section: Introductionmentioning
confidence: 97%